2017
DOI: 10.1007/s00441-017-2611-2
|View full text |Cite
|
Sign up to set email alerts
|

Toolbox in a tadpole: Xenopus for kidney research

Abstract: Xenopus is a versatile model organism increasingly used to study organogenesis and genetic diseases. The rapid embryonic development, targeted injections, loss- and gain-of-function experiments and an increasing supply of tools for functional in vivo analysis are unique advantages of the Xenopus system. Here, we review the vast array of methods available that have facilitated its transition into a translational model. We will focus primarily on how these methods have been employed in the study of kidney develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…Kidney disease is another very promising area in which Xenopus offers great potential, because the tadpole differentiates one fully functional nephron on either side, ideally suited to studying the various steps of kidney development from tubulogenesis to segmentation and active filtration, again in a one-sided manner with its internal control [Lienkamp et al, 2012;Hoff et al, 2013;Lienkamp, 2016]. Both these examples have recently been covered by excellent reviews, to which the interested reader is referred [Garfinkel and Khokha, 2017;Getwan and Lienkamp, 2017]. A large group of diverse genetic diseases that is particularly well qualified to be studied in Xenopus is represented by the so-called ciliopathies [Fliegauf et al, 2007;Mitchison and Valente, 2017].…”
Section: Doi: 101159/000490898mentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney disease is another very promising area in which Xenopus offers great potential, because the tadpole differentiates one fully functional nephron on either side, ideally suited to studying the various steps of kidney development from tubulogenesis to segmentation and active filtration, again in a one-sided manner with its internal control [Lienkamp et al, 2012;Hoff et al, 2013;Lienkamp, 2016]. Both these examples have recently been covered by excellent reviews, to which the interested reader is referred [Garfinkel and Khokha, 2017;Getwan and Lienkamp, 2017]. A large group of diverse genetic diseases that is particularly well qualified to be studied in Xenopus is represented by the so-called ciliopathies [Fliegauf et al, 2007;Mitchison and Valente, 2017].…”
Section: Doi: 101159/000490898mentioning
confidence: 99%
“…A number of transgenic lines are already available from the US and European resource centers (Xenbase.org; xenopusresource.org), and new ones can be generated fairly quickly [Aslan et al, 2017;Moreno-Mateos et al, 2017]. Candidate genes and alleles for human genetic disease are being identified at an enormous pace: analyses such as genome-wide association studies, GWAS, whole-exome sequencing, WES, and DNA and RNA sequencing from healthy and diseased tissues generate long lists of candidate genes and alleles that overwhelm biomedical researchers with the task of evaluating large data sets rapidly and at a manageable cost [MacArthur et al, 2014;Samocha et al, 2014;Getwan and Lienkamp, 2017]. The demand is for models to verify or discard candidate genes and to establish predictive models in which therapeutic options can be developed and tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, we wondered whether Gda might be important for kidney function. It has been demonstrated that an altered osmoregulatory function of the kidney leads to edema formation due to water retention (Wessely and Tran, 2011;Krneta-Stankic et al, 2017) and evaluation of edema has been widely used to assess kidney function (Getwan and Lienkamp, 2017;Krneta-Stankic et al, 2017). Thus, we used an antisense oligonucleotide to knock down (KD) gda by 50% (Fig.…”
Section: Xenopus Gda Is Strongly Expressed In the Embryonic Kidney Anmentioning
confidence: 99%
“…We developed a Xenopus model in which we could study braindependent events in embryogenesis: the brain is removed during early embryonic stages, but the animal can be kept alive and development continues. The ability of this vertebrate, a popular model for numerous biomedical contexts, [27][28][29][30][31][32][33][34] to survive and develop without a brain provides a unique opportunity to understand the role of the brain in diverse systems-level outcomes. Our prior research into brain-dependent developmental signaling revealed that the nascent brain, even before being fully formed, plays an instructive role in patterning somitic muscle and peripheral neural networks.…”
Section: Introductionmentioning
confidence: 99%